Research Status and Developing Trend of Gearbox Fatigue Test Rig System - Cheng Yanquan; Zhou Jianjun; Li Jing; Hu Tao (Jixie chuandong)
The research status of gearbox test rig system is reviewed at home and abroad. The problem of energy feedback for the gearbox fatigue test rig system is introduced and classified by the energy power flow.The state of the art of research achievements of gearbox test rig system are given as well as the basic working principles and working performances of various dynamometer test bed system are illustrated in detail. The advantages and disadvantages of various structures are compared,and the application scope of various dynamometer test rig system are summarized. The development trends of dynamometer test bed system are reviewed from the energy feedback load and intelligent control.